Dampak Perluasan Airside dalam Mendukung Operasional Penerbangan di Bandar Udara Sultan Muhammad Kaharuddin III, Sumbawa Besar - Usamah Daffa Ramadhan; Awan Awan (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2025)
In supporting the progress of an airport, there needs to be infrastructure development and expansion, such as airside expansion. Sultan Muhammad Kaharuddin III Airport has expanded its airside such as runway, taxiway, and apron. The expansion of the airside aims to increase flight capacity, improve flight operational safety, improve flight operational efficiency, and support tourism in Sumbawa Besar. This study uses a qualitative research method with primary data collection through interviews and observations, as well as secondary data through documents related to airside expansion. Data analysis techniques use data collection, data reduction, data presentation, and drawing conclusions. This study was conducted at Sultan Muhammad Kaharuddin III Airport. The results of the study show that there is an expansion of the airside at Sultan Muhammad Kaharuddin III Airport, such as the runway, taxiway, and apron which has been carried out in several years. This airside expansion has a positive impact on flight operations. Where the impact is an increase in the number of passengers, increasing flight capacity and adding flight routes, as well as increasing flight security and safety at Sultan Muhammad Kaharuddin III Airport..